2020
DOI: 10.3389/fpsyg.2020.566848
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Interaction Between Form and Motion Processing: A Review of Basic Research and Clinical Evidence

Abstract: A widely held view of the visual system supported the perspective that the primate brain is organized in two main specialized streams, called the ventral and dorsal streams. The ventral stream is known to be involved in object recognition (e.g., form and orientation). In contrast, the dorsal stream is thought to be more involved in spatial recognition (e.g., the spatial relationship between objects and motion direction). Recent evidence suggests that these two streams are not segregated but interact with each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 142 publications
0
11
0
2
Order By: Relevance
“…По-видимому, это связано с тем, что в случае предъявления ломаных в динамическом режиме испытуемый воспринимает не серию элементов (сегментов ломаной), а движущуюся точку. Как показывает ряд исследований, мозговые системы, обеспечивающие восприятие и хранение формы на основе статического изображения и движущегося объекта, различны (Kriegeskorte et al, 2003;Donato et al, 2020). Не исключено, что реконструкция формы на основе движения сложнее и поэтому сопряжена с бjльшим числом ошибок.…”
Section: точность воспроизведенияunclassified
See 1 more Smart Citation
“…По-видимому, это связано с тем, что в случае предъявления ломаных в динамическом режиме испытуемый воспринимает не серию элементов (сегментов ломаной), а движущуюся точку. Как показывает ряд исследований, мозговые системы, обеспечивающие восприятие и хранение формы на основе статического изображения и движущегося объекта, различны (Kriegeskorte et al, 2003;Donato et al, 2020). Не исключено, что реконструкция формы на основе движения сложнее и поэтому сопряжена с бjльшим числом ошибок.…”
Section: точность воспроизведенияunclassified
“…Так, при построении внутренней репрезентации на основе статической пространственной информации, как это имеет место, например, при копировании текста, изменения активности мозга обнаружены преимущественно в задней теменной коре (PPC) (Lehnert, Zimmer, 2008), в то время как при запечатлении динамической зрительной информации наблюдается иная картина. Чувствительные к движению нейроны областей MT/MST, по-видимому, участвуют в системе рабочей памяти у приматов (Kriegeskorte et al, 2003;D'Esposito, Postle, 2015;Donato et al, 2020;Curtis, Sprague, 2021). Интерференция текущей оценки направления движения и внутренней репрезентации движения другого направления, обнаруженная при исследовании на людях, указывает на то, что мозговая система рабочей памяти включает сенсорные области, чувствительные к направлению движения (Kang et al, 2011).…”
Section: Introductionunclassified
“…According to Ungerleider and Mishkin [1], these two visual streams were physically segregated yet functionally independent. However, several later research studies disputed this perspective, advocating an integrated view of the visual brain [2][3][4][5][6][7][8][9]. Dynamic Glass patterns (GPs) [10] and random dot kinematograms (RDKs) are two types of visual stimuli commonly employed to assess the functional properties of the dorsal and ventral streams.…”
Section: Introductionmentioning
confidence: 99%
“…Although dynamic GPs include local and global form aspects determined by dipole orientation, they are primarily connected to motion perception circuits in the brain [12]. Dynamic GPs have been employed in several investigations to offer insight into how form-motion interactions occur in the human visual cortex [2,4,8,9,[12][13][14][15][16][17]. RDKs, in contrast to dynamic GPs, are made up of single dots that follow a definite path across the sequence of frames.…”
Section: Introductionmentioning
confidence: 99%
“…This is followed by the global pooling of local motion/orientation resulting in the perception of overall direction/orientation of the whole pattern in the higher cortical such as MT for RDK (Morrone, Burr & Vaina, 1995) and V4 for Glass patterns (Dakin, 1997, Wilson & Wilkinson, 1998)global processing. More recently, however, it has been suggested that interaction of information between motion and form is required for stable visual perception where motion information can help perceive form better or vice versa (Donato, Pavan & Campana, 2020, Goodale, 2011, Mather, et al, 2012, Ross, 2004, Ross, Badcock & Hayes, 2000, Sincich & Horton, 2005). The most dramatic example of how motion influences form perception is the demonstration of biological motion, where the biological form is only perceived when motion cues are introduced to the static pattern of dots (Johansson, 1973).…”
Section: Introductionmentioning
confidence: 99%